2016
DOI: 10.1038/nmicrobiol.2016.127
|View full text |Cite
|
Sign up to set email alerts
|

Microbial mercury methylation in Antarctic sea ice

Abstract: Atmospheric deposition of mercury onto sea ice and circumpolar sea water provides mercury for microbial methylation, and contributes to the bioaccumulation of the potent neurotoxin methylmercury in the marine food web. Little is known about the abiotic and biotic controls on microbial mercury methylation in polar marine systems. However, mercury methylation is known to occur alongside photochemical and microbial mercury reduction and subsequent volatilization. Here, we combine mercury speciation measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
179
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(184 citation statements)
references
References 84 publications
5
179
0
Order By: Relevance
“…Capturing the seasonality of atmospheric Hg in the Arctic using GEOSChem required parameterization of unique sea ice, oceanic, and riverine dynamics (Fisher et al, , 2013Y. Zhang et al, 2015); a similar analysis for the Southern Ocean region, with its distinct productivity dynamics impacting Hg cycling (e.g., Cossa et al, 2011;Gionfriddo et al, 2016), has not yet been performed.…”
Section: Seasonalitymentioning
confidence: 99%
“…Capturing the seasonality of atmospheric Hg in the Arctic using GEOSChem required parameterization of unique sea ice, oceanic, and riverine dynamics (Fisher et al, , 2013Y. Zhang et al, 2015); a similar analysis for the Southern Ocean region, with its distinct productivity dynamics impacting Hg cycling (e.g., Cossa et al, 2011;Gionfriddo et al, 2016), has not yet been performed.…”
Section: Seasonalitymentioning
confidence: 99%
“…However, significant positive correlations have been found between K meth and %MeHg in many environments (Drott et al 2008), and %MeHg values in boreal wetlands tracked the ratio of K meth to K demeth (Tjerngren et al 2012a), suggesting that if both rates are measured, steady state net MeHg production rates can be estimated. Very recently, measurements of potential rates have been replaced with measurements of the genetic potential of the microbial community (e.g., Gionfriddo et al 2016) due to the recent discovery of a gene cluster responsible for mercury methylation (see below), and developments in this area will be useful in addressing many of the questions previously addressed using the measurements of potential rates. While methylation may occur abiotically in some environments (Celo et al 2006;Eckley and Hintelmann 2006;Monperrus et al 2007a;Perrot et al 2013), biotic methylation by microbes is the primary source of MeHg in aquatic environments.…”
Section: Why Is Net Methylmercury Production Important and How It Is mentioning
confidence: 99%
“…In fact, studies using molecular techniques to directly examine potential sites of methylation are currently being published. For example, Gionfriddo et al (2016) have identified Antarctic sea ice as a possible environment conducive to the growth of a marine microaerophilic bacterium (Nitrospina) by isolating the hgcAB genes Sulfate reducing bacteria inhibitors (Compeau and Bartha 1985;Kerry et al 1991;Gilmour et al 1992;Choi and Bartha 1993;Choi et al 1994) Correlations with SO 4 concentrations (Devereux 1996;King et al 1999; Eckley and Hintelmann 2006) Presence of hgc gene cluster Parks et al 2013;Sonke et al 2013;Podar et al 2015) Stable isotope assays only Bacteria Deltaproteobacteria Geobacter metallireducens Desulfuromonas palmitatis Geobacter hydrogenophilus Geobacter sulfurreducens Where does methylation occur?…”
Section: Why Is Net Methylmercury Production Important and How It Is mentioning
confidence: 99%
“…Being contrary to organic degradation, mercury is not biodegradable and can be bio‐accumulated along the food chain. Hg(II) is a solvated ion with high cellular toxicity and carcinogenic potential and becomes stronger toxicity speciation through microbial mercury methylation even in polar marine environments (Gionfriddo et al, ). These organic mercury speciations contain methylmercury, ethylmercury, and phenylmercury.…”
Section: Introductionmentioning
confidence: 99%
“…cellular toxicity and carcinogenic potential and becomes stronger toxicity speciation through microbial mercury methylation even in polar marine environments (Gionfriddo et al, 2016). These organic mercury speciations contain methylmercury, ethylmercury, and phenylmercury.…”
mentioning
confidence: 99%